Simulation and Implementation of a Wireless Metal Detector with Variety of Flexible Responses- A Solution to Extensive Security Threats - Awais Ahmed; Hassan Sarwar (Bulletin of Electrical Engineering and Informatics, 2016)
We proposed a design of a wireless metal detector in this research article. A system is designed which offers a variety of electrical equipments necessary for a privatized metal sensor. The main objective of this research is to provide a mature solution to the recent security threads all over the world by designing a localized wireless metal detection system. Different analysis has been shown graphically in this article. In addition, the system is kept flexible to respond to a security threat e.g. in case of a metal detection. The case study chosen for this article is Pakistan, a country facing extensive threats in the age of globalization.